Isolation of multi-drug resistant Klebsiella sp. from bovine mastitis samples in Rangpur, Bangladesh - Salauddin, Md; Akter, Mir Rowshan; Hossain, Md Khaled; Rahman, Md Mostafizer (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of this study was to identify the multi-drug resistance (MDR) Klebsiella sp. from mastitis milk samples. Materials and Methods: In the current research, 48 clinical mastitis milk samples were collected from Rangpur division, Bangladesh. Confirmation of bovine mastitis (BM) was done by the California Mastitis Test (CMT). All the CMT positive isolates were subjected for the identification of Klebsiella sp. using through a series of cultural and biochemical tests. MDR Klebsiella sp. isolates were determined using the disk diffusion method, and minimum inhibitory zones were measured by following Clinical and Laboratory Standards Institute. MDR patterns of the isolates were also subjected to study by using housefly (Musca domestica). Results: Among the isolates, 62.5% (n = 30/48) revealed the presence of Klebsiella sp. Eight antimicrobial agents including Amoxicillin, Novobiocin, Erythromycin, Vancomycin, Cephradine, Tetracycline, Bacitracin, Methicillin, and housefly (M. domestica) showed complete resistance to Klebsiella sp. On the other hand, Chloramphenicol, Gentamicin, Ciprofloxacin, Azithromycin, Norfloxacin, Levofloxacin, and Nalidixic acid showed sensitivity. Conclusion: This study helps to treat BM with effective antibiotics and helps in an epidemiological study in Rangpur division as well as helps to create public health awareness. J. Adv. Vet. Anim. Res., 6(3): 362-365, September 2019